2008
DOI: 10.1167/8.13.12
|View full text |Cite
|
Sign up to set email alerts
|

The attentional blink in amblyopia

Abstract: Amblyopia is a disorder of visual acuity in one eye, thought to arise from suppression by the other eye during development of the visual cortex. In the attentional blink, the second of two targets (T2) in a Rapid Serial Visual Presentation (RSVP) stream is difficult to detect and identify when it appears shortly but not immediately after the first target (T1). We investigated the attentional blink seen through amblyopic eyes and found that it was less finely tuned in time than when the 12 amblyopic observers v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 29 publications
4
50
1
1
Order By: Relevance
“…In a different type of tracking task, in which the ability to track deviations in linear trajectories was assessed, a small deficit was observed in the amblyopic but not the fellow eye in a group of six adults with strabismic and/or anisometropic amblyopia (Tripathy & Levi, 2008). The deficit in multiple-object tracking in amblyopia is consistent with other deficits on high-level tasks requiring attentive processing, including object enumeration (Sharma, Levi, & Klein, 2000) and the attentional blink (Asper, Crewther, & Crewther, 2003;Popple & Levi, 2008).…”
Section: Multiple-object Trackingmentioning
confidence: 56%
“…In a different type of tracking task, in which the ability to track deviations in linear trajectories was assessed, a small deficit was observed in the amblyopic but not the fellow eye in a group of six adults with strabismic and/or anisometropic amblyopia (Tripathy & Levi, 2008). The deficit in multiple-object tracking in amblyopia is consistent with other deficits on high-level tasks requiring attentive processing, including object enumeration (Sharma, Levi, & Klein, 2000) and the attentional blink (Asper, Crewther, & Crewther, 2003;Popple & Levi, 2008).…”
Section: Multiple-object Trackingmentioning
confidence: 56%
“…Indeed, if we were to systematically manipulate attention and test amblyopes on a series of tasks, attention-related deficits may manifest further along the visual pathways or for higher level cognitive functions. For instance, in tasks using crowded and dynamic stimulus displays thought to involve higher level forms of attention, e.g., attentional tracking of multiple object displays (Ho et al, 2006) and the attentional blink paradigm (Popple & Levi, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…the attentional blink (Popple & Levi, 2008), numerosity estimation (Sharma, Levi, & Klein, 2000), and multiple object tracking (Ho et al, 2006; Tripathy & Levi, 2008). 1 These deficits may be a consequence of the anomalous visual input amblyopes receive during development, which leads to abnormal visual processing.…”
Section: Introductionmentioning
confidence: 99%
“…Under everyday binocular viewing conditions, an amblyope would almost never initiate a saccade toward a target seen in the amblyopic eye (Popple & Levi, 2008). For one thing, there is not much to be gained by shifting the amblyopic fovea to a peripheral target.…”
Section: Discussionmentioning
confidence: 99%
“…Because the amblyopic eye does not determine the saccadic target, it probably has little influence on selective attention during binocular viewing, and may suffer from inadequate command of attention even during monocular viewing. Several studies have found abnormalities in the control of attention by the amblyopic eye (Farzin & Norcia, 2011; Kiorpes, Pham, & Carrasco, 2012; Popple & Levi, 2008; Sharma, Levi, & Klein, 2000). Lai, McKee, Hou, and Verghese (2013) found that the amblyopic eye could use cued attention to enhance contrast sensitivity, but that the shift in attention to the cued site was delayed, compared to normal observers.…”
Section: Discussionmentioning
confidence: 99%